AGING IN THE PERCEPTION OF YOUNG PEOPLE - SELECTED CORRELATES OF PERSONALITY - Kurtyka-Chałas, Justyna (Uniwersyteckie Czasopismo Socjologiczne, 2016)
In the context of the demographic and psychosocial changes capturing the factors that are relevant to the process of perception of the aging process and their own old age becomes a significant problem. The article discusses the results of the study conducted on a group of 430 people on the factors determining the perception of old age by young people. Presented selected results relate to the personality correlates of perception of the aging process.